2D Nanopatterning: 2D Metal Chalcogenide Nanopatterns by Block Copolymer Lithography (Adv. Funct. Mater. 50/2018). (10th December 2018) - Yun, Taeyeong; Jin, Hyeong Min; Kim, Dong‐Ha; Han, Kyu Hyo; Yang, Geon Gug; Lee, Gil Yong; Lee, Gang San; Choi, Jin Young; Kim, Il‐Doo; Kim, Sang Ouk
Abstract : In article number1804508, Sang Ouk Kim and co‐workers present a reliable and effective nanopatterning strategy for 2D transition metal dichalcogenides via block copolymer (BCP) lithography. By exploiting various BCP templates, diverse nanostructures, including nanomeshes, nanodots, and nanowire arrays, are demonstrated with wafer‐scale scalability. Edge‐exposed MoS2 nanomeshes exhibit superior sensitivity and reversibility for NO2 gas sensing.